Breakfast Habits, Physical Activity Levels, And Their Relationship To The Nutritional Status Of Sixth Grade Students At Sdn Banjarbendo Elementary School, Sidoarjo District - Nailatul Fitriyyati; Anindya Mar'atus Sholikhah; Rahayu Dewi Soeyono; Choirul Anna Nur Afifah (CV. AFDIFAL MAJU BERKAH, 2026)
Breakfast habits and physical activity are important factors in determining the nutritional status and long-term health of school-aged children. Based on preliminary data from April 2025 at Banjarbendo Elementary School in Sidoarjo, 46 ​​students (63%) had poor breakfast habits and 36 students (53%) had low levels of physical activity. Skipping breakfast can lead to an imbalance in daily energy intake, while low levels of physical activity can increase the risk of health problems and reduce children's fitness. This study aims to analyze the relationship between breakfast habits and physical activity levels and the nutritional status of sixth-grade students at Banjarbendo Elementary School. The study used a cross-sectional design with a sample size of 74 students, consisting of 47 boys and 27 girls. The independent variables in this study were breakfast habits and physical activity levels, while the dependent variable was nutritional status based on BMI/Age. Data were collected through questionnaires, interviews, and anthropometric measurements. Univariate and bivariate analyses were performed using the Chi-Square test. The results of the univariate analysis showed that the majority of respondents (41 students) had good breakfast habits, while 33 students (44.6%) had poor breakfast habits. Regarding physical activity, the majority of respondents were in the low and very low categories, at 63.5% and 21.6%, respectively. The results of the bivariate analysis showed no significant relationship between breakfast habits and students' nutritional status (p-value = 0.283). However, there was a significant relationship between physical activity levels and the nutritional status of sixth-grade students at Banjarbendo Elementary School (p-value = 0.020). This research is expected to serve as a basis for developing promotive and preventive efforts in the school environment, particularly through nutrition education and the promotion of regular physical activity to support optimal student growth and health.